ANALISIS PENDAHULUAN PENGEMBANGAN BAHAN AJAR MATEMATIKA BERBASIS DISCOVERY LEARNING PADA MATERI PECAHAN UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS V SD - Sherlyane Hendri; Ary Kiswanto Kenedi (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
Students’ problem solving ability at any school is still in low category. That is due to student weakness to understand any mathematical problems that linked to the real life around them. One of any cause of this problem is  mathematics lesson equipments development and its utilization by teacher are not optimal yet. To solve this problem, mathematics teachers should develop mathematics lesson equipments based on discovery learning for class V student at Elementary school that sutisfied validity, practicality, and efectiveness criteria. This is a development research with 4D models consisting of Define, Design, Develop, and Disseminate. In preliminary research for Define stage, researcher takes analysis of needs, analysis of curiculum, and analysis of mathematic concepts. Techniques of data collection through interview with teacher mathematics, questionnaire learners, curriculum analysis. Based on the analysis found that the needs of learners in the form of new learning model in addition to conventional learning are better able to increase problem solving ability of able to improve students' problem solving abilities to achieve desired goals and then designed a mathematics teaching material based on discovery learning.Keywords : Problem solving ability, Discovery Learning, 4-D model